Initiating oral fingolimod treatment in patients with multiple sclerosis. (July 2013) - Singer, Barry A.
Fingolimod, the first oral disease-modifying therapy (DMT) approved for the treatment of multiple sclerosis (MS) and the only sphingosine 1-phosphate receptor modulator approved for any disease state, represents an important addition to the expanding DMT options for patients with MS. In three large phase III clinical trials, fingolimod 0.5 mg reduced relapses by approximately half compared with either placebo or weekly intramuscular interferon β1a. The risks associated with the use of fingolimod include first-dose bradycardia, macular edema, and elevation of liver enzymes; fingolimod may increase the risk of infections, some serious in nature, and potentially cause fetal harm. Breakthrough disease or intolerance of injectable medications may be factors that influence the initiation of fingolimod. Identification of potential patients suitable for fingolimod treatment requires a thorough understanding of the potential risks and the particular fingolimod indication of the national authority. To minimize risk, recommended baseline assessments that should be made prior to fingolimod initiation include complete blood count, liver transaminase levels, total bilirubin levels, electrocardiogram (ECG), ophthalmologic examination, varicella zoster infection status, and for women, childbearing potential. First-dose observation is required for all patients for at least 6 h, with hourly pulse and blood pressure measurements and ECG before and 6 h after the first dose. In the European Union, continuous telemetry monitoring is recommended. Healthcare providers should be aware of the potential for symptomatic bradycardia and the need for continuous overnight ECG monitoring for those at higher risk for bradycardia. With experience in over 63, 000 patients and over 73, 000 patient-years of exposure in clinical trials and postmarketing use, the benefits and full safety profile of fingolimod continue to become better elucidated. This information will enable healthcare providers to initiate fingolimod in appropriately selected and screened patients with MS.